Hubungan Self-Efficacy dan Kepatuhan Pengobatan terhadap Asthma Control Test pada Pasien Asma - Girsang, Isah Masdiana; Suza, Dewi Elizadiani; Tarigan, Amira Permatasari (Journal of Telenursing (JOTING), 2024)
This research aims to examine the relationship between self-efficacy and treatment compliance with the asthma control test in asthma patients. This type of research is quantitative using descriptive correlational methods. The number of samples in this study that met the inclusion criteria was 44 patients at the North Sumatra University Hospital, Medan, with the sampling technique used was consecutive sampling. The instruments used in this research were self-efficacy instruments, medication adherence instruments namely MMAS-8 and Asthma control test measurements by (ACT) by the American Lung Association (ALA) questionnaire. Data analysis in this research consists of Univariate analysis and Bivariate analysis using the Chi-Square statistical test. The research results showed that self-efficacy and the Asthma Control Test (ACT) obtained a value of p = 0.01 < 0.05 and the value of treatment compliance with the Asthma Control Test (ACT) obtained a value of p = 0.051 < 0.05. In conclusion, there is no significant relationship between self-efficacy and treatment compliance with the Asthma Control Test (ACT) in asthma patients. Keywords: Asthma Control Test, Treatment Compliance, Self-Efficacy.